Anodization of Ti6Al4V in Water-Ethylene Glycol Solution Containing NH4F and Its Corrosion Behavior in Ringer's Solution - Turu, Irem Cemre; Cansever, Nurhan (ELSEVIER, 2022)
In this study, Ti6Al4V samples were anodized at room temperature with a constant voltage of 30 V for 3 hours in ethylene glycol solutions containing 0.25% NH4F by weight and 2.5%, 5% and 10% deionized H2O by volume. After the anodization, the structure and crystallinity of the oxide layers were investigated by Field-Emission Scanning Electron Microscopy and X-ray diffraction methods, respectively. According to the findings, all anodized samples exhibited crystalline TiO2 nanotubular structures composed of rutile and anatase. FESEM analyzes showed that the thickness of the nanotube layer decreased accordingly with increasing H2O content in the organic anodizing medium. For comparison, electrochemical behaviors of the anodized and untreated Ti6Al4V samples were evaluated in Ringer's solution at 37 degrees C by electrochemical impedance spectroscopy and potentiodynamic polarization techniques. According to the results, the anodized samples which had nanotubular structures, exhibited better corrosion behavior than untreated Ti6Al4V. Furthermore, electrochemical analyses also revealed that increase of H2O content in ethylene glycol lowered the corrosion resistance of the anodized samples by affecting the morphology, structure and the length of the nanotubes.
Keywords: Ti6Al4V; TiO2 nanotubes; Impedance Spectroscopy; Ringer's solution; ELECTROCHEMICAL IMPEDANCE; NANOTUBES; GROWTH; ALLOY; FILM; MORPHOLOGY; OXIDE; Electrochemistry